2021
DOI: 10.31557/apjcp.2021.22.3.827
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Second Hand Tobacco Smoke among 12 year old Adolescents in Mangalore, Karnataka – A Descriptive Study

Abstract: Although many countries of the World have passed laws making workplaces, public places, and restaurants smoke-free, still millions of children and adults continue to breathe second hand tobacco smoke (SHS) (CDC, 2007). According to the World Health Organization (2020), the health of almost half of the world's children is affected by exposure to environmental tobacco smoke (ETS). SHS exposure has been linked to a variety of serious diseases in adults as well as in children, such as coronary heart disease, lung … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
0
6
1
Order By: Relevance
“…In the phase 1 part of the study ( 21 ), 236 participants reported that somebody who lived with them smoked tobacco. Among them, 142 were willing to participate in this phase of the study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the phase 1 part of the study ( 21 ), 236 participants reported that somebody who lived with them smoked tobacco. Among them, 142 were willing to participate in this phase of the study.…”
Section: Resultsmentioning
confidence: 99%
“…This study is a component of a multiphase study that was conducted among 12-year-old school children in Mangalore, India. The first phase was a descriptive cross-sectional study that used a cluster random sampling of all schools, which is described in detail elsewhere ( 21 ). The 12-year-olds in the selected schools who met the inclusion criteria, i.e., who consented to participate in the study and those participants whose parents gave written informed consent and they themselves give informed assent, were given a questionnaire.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…or by the side stream of a cigarette. 5 Based on these findings, it is pivotal to design school-based prevention programmes using a multi-stakeholder approach, with high school teachers serving as a crucial stakeholder. This study fills a gap in the literature regarding the lack of similar studies among high school teachers by focusing on their knowledge and behaviour towards SHS.…”
Section: Discussionmentioning
confidence: 99%
“…1 According to global youth tobacco survey (GYTS-4), conducted in 2019 by the international institute for population sciences (IIPS) under the Ministry of Health and Family Welfare (MoHFW) the median age of initiation to cigarette and bidi-smoking, and smokeless tobacco use were 11.5 years, A study by Rao et al done in Mangalore to assess the exposure to second hand tobacco smoke among 12-yearold adolescents reported that 28.6% of children were exposed to SHS. 5 Aswathy et al reported second hand smoke exposure among 20.3% of high school students in Ernakulam district of Kerala. 6 A cross sectional study done by Rustagi et al among class 7 and class 8 school students pointed out that though children reported smoking from other people was harmful (89%) and discussion about harmful effects of smoking was carried out by school authorities (73.2%) and families (75.9%) of adolescents yet attitude towards SHS among adolescents was favourable and was considered helpful in enhancing socialization among boys (73.10%) and making personality attractive among girls.…”
Section: Introductionmentioning
confidence: 99%